2018
DOI: 10.1007/s12098-018-2753-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Growth in Congenital Adrenal Hyperplasia

Abstract: Monitoring growth and puberty in children with CAH is critical for optimizing final height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…It is still possible that a few additional children with mild disease were missed in this cohort. Similar findings are echoed in a retrospective case series from India [31], where precocious puberty and growth failure were reported in most children. CAH is the most common cause of female ambiguity which presents during adolescence [14,16].…”
Section: Disease Burden In India and Need Of Nbssupporting
confidence: 78%
“…It is still possible that a few additional children with mild disease were missed in this cohort. Similar findings are echoed in a retrospective case series from India [31], where precocious puberty and growth failure were reported in most children. CAH is the most common cause of female ambiguity which presents during adolescence [14,16].…”
Section: Disease Burden In India and Need Of Nbssupporting
confidence: 78%
“…The mean height SDS was described as –0.6. A study from western India described the faltering of height SDS from –0.1 to –0.3 and –0.4 to –0.5 in boys and girls with CAH, respectively [ 18 ]. They described the final height Z-score in a subset at –1.8 in salt wasting CAH and –1.6 in simple virilizing CAH.…”
Section: Discussionmentioning
confidence: 99%
“…It is pivotal that the initiation of GnRH analogue therapy is individualized for every case. Height prediction using Bayley Pinneau tables has recently been reported to be accurate for Indian children with CAH [ 18 ]. These children need to be followed up until they reach their adult height.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a delay in diagnosis and suboptimal management unless timely referral occurs to a centre where such expertise exists. Another recent Indian study has reported a mean final height SDS of −2.06 ± 1.1 for boys and − 1.47 ± 1.1 for girls with CAH [6].…”
mentioning
confidence: 91%